Hawking y los agujeros negros en 90 minutos - Strathern, Paul, 1940-; Tena, Pedro; Strathern, Paul, 1940- (Tres Cantos, Madrid, España : Siglo XXI de España Editores, S.A., 2014)
This brief biography of scientist Stephen Hawking focuses on his theories of black holes.
Online resource; title from ePub title page (Digitalia, viewed June 28, 2017)
Keywords: Hawking, Stephen, -- 1942-; Black holes (Astronomy); Physicists -- Great Britain -- Biography; Electronic books